2017
DOI: 10.4172/2329-9053.1000138
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Mouth Dissolving Film of Ondansetron Hydrochloride Using Hpmc E 5 in Combination with Taro Gum and Other Commercially Available Gums

Abstract: Objective: Ondansetron hydrochloride belongs to the class of 5HT3 antagonists. It is approved by United States Food and Drug Administration (US FDA) to control chemotherapyinduced nausea and vomiting. The oral bioavailability of ondansetron is approximately 60%, indicating first pass metabolism. The present research work was carried out with an objective to increase the bioavailability of the drug ondansetron hydrochloride by developing its mouth dissolving film using taro gum in combination with HPMC E5.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In 2014, Costa et al suggested chitosan-based mucoadhesive film along with photodynamic therapy to boost the retention of 10.0% of 5-ALA in tumor tissue, and found it to be a reliable aid in oral cancer therapy for local drug delivery [11]. Pawar and Kamat developed and evaluated the mouth dissolving film of the drug 'ondansetron hydrochloride' using taro gum and observed an improvement in its bioavailability, release, disintegration time, and tensile strength in comparison to the conventional methods [12]. Jin Bao Z et al investigated the role of mucoadhesive patches loaded with methotrexate (MTX) liposomes in the local drug delivery system for oral cancer, and found it to exhibit suitable bio-adhesive properties and prolonged release time [13].…”
Section: Fast Dissolving Oral Thin Filmsmentioning
confidence: 99%
“…In 2014, Costa et al suggested chitosan-based mucoadhesive film along with photodynamic therapy to boost the retention of 10.0% of 5-ALA in tumor tissue, and found it to be a reliable aid in oral cancer therapy for local drug delivery [11]. Pawar and Kamat developed and evaluated the mouth dissolving film of the drug 'ondansetron hydrochloride' using taro gum and observed an improvement in its bioavailability, release, disintegration time, and tensile strength in comparison to the conventional methods [12]. Jin Bao Z et al investigated the role of mucoadhesive patches loaded with methotrexate (MTX) liposomes in the local drug delivery system for oral cancer, and found it to exhibit suitable bio-adhesive properties and prolonged release time [13].…”
Section: Fast Dissolving Oral Thin Filmsmentioning
confidence: 99%